UM MODELO DE DETECÇÃO DE INTRUSÃO PARA AMBIENTES DE COMPUTAÇÃO EM NUVEM - ARAÚJO, Josenilson Dias (2013)
The elasticity and large consumption of computational resources are becoming attractive for intruders to exploit the cloud vulnerabilities to launch attacks or have access of private and privileged data of cloud users. In order to effectively protect the cloud and its users, the IDS must have the capability to quickly scale up and down the quantity of sensors according to the resources provisioned, besides of isolating the access to the system levels and infrastructure. The protection against internal cloud threats must be planned because of the non-adequate threatening identification system in most protection systems. For this, the proposed solution uses virtual machines features as fast recovery, start, stop, migration to other hosts and cross-platform execution in IDS based VM, to monitor the internal environment of the cloud virtual machines by inserting data capture sensors at the local network of the VM users, this way, it can detect suspicious user behaviors.